Effect of Bioaccumulation of Heavy Metals in Oreochromis niloticus Tissues of an Urban Lake in Southern Brazil - Domingues, Cinthia Eloise; da Silva, Cleber Pinto; Stremel, Tatiana Roselena de Oliveira; Zittel, Rosimara; Kordiak, Januário; Bozza, Dandie Antunes; Ribeiro, Ciro Alberto Oliveira; de Campos, Sandro Xavier (Orbital: The Electronic Journal of Chemistry, 2019)
In this study, the effect of the bioaccumulation of metals on Oreochromis niloticus tissues was evaluated. Significant Co, Mn and Ni concentrations were found in the lake water near the fertilizer industries. In the sediment was identified the presence of Cd (4.612 ± 0.930 mg kg-1), Ni (46.847 ± 3.801 mg kg-1) and Zn (865.534± 89.437) mg kg-1) in concentrations above the probable effect level (PEL). For Cu (141.963 ± 5.148 mg kg-1) and Pb (53.362 ± 6.621 mg kg-1) concentrations between the threshold effect (TEL) or probable effect (PEL) levels. Regarding Oreochromis niloticus tissues, the concentration of metals in the liver was higher than found in muscle. The biomarkers indicated that the hepatic cells of Oreochromis niloticus are under oxidative stress, explained by the higher levels of reduced glutathione (GSH), lipid peroxidation (LPO) and protein carbonylation (PCO) when compared to control fish tissues. The set of biomarkers presented in this study contribute to define the effects of the bioaccumulation of metals in Oreochromis niloticus tissues. DOI: http://dx.doi.org/10.17807/orbital.v11i7.1366